2010
DOI: 10.1002/app.32027
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of high temperature resistance interpenetrating polymer network

Abstract: Interpenetrating polymer network (IPN) polymer has been prepared by blending silicone resin polymer with the organic polymers such as polypyrrole [PPy] and polythiophene [PTh]. The IPNs were characterized by FTIR, NMR, and TGA/DSC analysis. The heat resistance performance of these IPNs were evaluated as per ASTM D2485. The result indicates that the IPN based on silicone-PTh has got superior heat resistant property than silicone-PPy. The electrochemical impedance measurements showed that the corrosion resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…When comparing curves c and d in Figure , the spectra are mainly unchanged except the small band at 1270 cm −1 , which is due to OC 2 H 5 on the SiOC 2 H 5 groups that disappeared at 600°C. The small absorption peak at 1270 cm −1 and the small weight loss of the DTG spectra at 520°C are consistent with the small amount of SiOC 2 H 5 groups present in the silicone resin, which is demonstrated from the analyses of C1s XPS of sample BSR‐1#, the smallest area (5.5% of total area) of the peak at 285.89 eV corresponding to C atoms from SiOC 2 H 5 groups owing to incompletely hydrolyzed. In the other hand, the relative high binding energy in XPS of this kind of C atoms (SiOC 2 H 5 ) also indicates that the connection of OC in this groups are more stable, which is consistent with the relative high temperature for the second degradation stage in DTG thermogram in Figure .…”
Section: Resultssupporting
confidence: 73%
“…When comparing curves c and d in Figure , the spectra are mainly unchanged except the small band at 1270 cm −1 , which is due to OC 2 H 5 on the SiOC 2 H 5 groups that disappeared at 600°C. The small absorption peak at 1270 cm −1 and the small weight loss of the DTG spectra at 520°C are consistent with the small amount of SiOC 2 H 5 groups present in the silicone resin, which is demonstrated from the analyses of C1s XPS of sample BSR‐1#, the smallest area (5.5% of total area) of the peak at 285.89 eV corresponding to C atoms from SiOC 2 H 5 groups owing to incompletely hydrolyzed. In the other hand, the relative high binding energy in XPS of this kind of C atoms (SiOC 2 H 5 ) also indicates that the connection of OC in this groups are more stable, which is consistent with the relative high temperature for the second degradation stage in DTG thermogram in Figure .…”
Section: Resultssupporting
confidence: 73%
“…The AFM morphology showed that the IPN had smooth glossy and heterogeneous microstructures. 25 The silicon resin used for this preparation was nondrying type with molecular weight 4000. The pigments used for this formulation were commercial TiO 2 and SiO 2 with the pigment loading of 15 PVC.…”
Section: Preparation Of Micropigmented Coatingsmentioning
confidence: 99%
“…[4] They show excellent thermal stability and mechanical properties because of a synergistic effect induced by the forced compatibility of the individual components. [5][6][7] Polyurethane/epoxy resin (PU/EP) IPNs, which integrate the advantages of polyurethane and epoxy resin, show relatively excellent thermal and mechanical properties. In recent years, much attention has been paid to them and their modification.…”
Section: Introductionmentioning
confidence: 99%